Translating High-Frame-Rate Imaging into Clinical Practice: Where Do We Stand? - Popescu Aniela; Bézy Stéphanie; Voigt Jens-Uwe (Sciendo, 2023)
Continuous developments in cardiovascular imaging, software, and hardware have led to technological advancements that open new ways for assessing myocardial mechanics, hemodynamics, and function. The technical shift from clinical ultrasound machines that rely on conventional line-per-line beam transmissions to ultrafast imaging based on plane or diverging waves provides very high frame rates of up to 5000 Hz with a wide variety of potential new applications, including shear wave imaging, ultrafast speckle tracking, intracardiac flow imaging, and myocardial perfusion imaging. This review provides an overview of these advances and demonstrates potential applications and their possible added value in clinical practice.